The Incident Command System: a literature review. Issue 1 (13th August 2015) - Jensen, Jessica; Thompson, Steven
Abstract : Given the foundational and the fundamental role that the Incident Command System (ICS) is intended to play in on‐scene response efforts across the United States, it is important to determine what is known about the system and how this is known. Accordingly, this study addresses the following research question: 'How has research explored the ICS?'. To probe this question, a methodological review of the scant, but widening, pool of research literature directly related to the ICS was conducted. This paper reports on the findings of the analysis related to the focus, theoretical frameworks, population and sampling, methods, results, and conclusions of the existing research literature. While undertaken using different methodological approaches, the ICS research suggests that the system may be limited in its usefulness. In addition, the paper discusses the implications of the research for the state of knowledge of the system and for the direction of future research.